STUDI MENGENAI CITY BRANDING KOTA YOGYAKARTA SEBAGAI KOTA PELAJAR DI INDONESIA - Yu, Steffanie; Setiyaningrum, Ari (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2019)
This study has a purpose to analyze the influence of attitude towards brand, brand uniqueness, and brand personality on self-brand connection and the influence of self-brand connection on brand advocacy. This study also analyzed the mediation of self-brand connection in the influence of attitude towards brand, brand uniqueness and brand personality on brand advocacy. The data collection is conducted by using the survey method, through the distribution of questionnaires to 128 immigrant student respondents who study in Yogyakarta City. The sampling method used is the non-probability sampling with the purposive sampling technique. By using the structural equation model with the AMOS statistics software, this study found that the attitude towards brand, brand uniqueness and brand personality have a positive influence on self-brand connection and self-brand connection has a positive influence on brand advocacy. Self-brand connection has also been proven to be capable of mediating the influence of attitude towards brand, brand uniqueness, and brand personality on brand advocacy. Keywords: attitude toward brand, brand uniqueness, brand personality, self-brand connection, brand advocacy.
Keywords: attitude toward brand, brand uniqueness, brand personality, self-brand connection, brand advocacy